Digital technologies as enablers of universal design for learning: higher education students' perceptions in the context of SDG4 - María Guadalupe Veytia Bucheli; José Gómez-Galán; Maritza Librada Cáceres Mesa; Luis López Catalán (Discover Sustainability)
Abstract Digital technologies are essential for transforming educational environments, particularly in higher education. These tools have revolutionized information access and enable flexible approaches within Universal Design for Learning (UDL). This educational model integrates findings from educational practice, research, learning theories, technological advances, and neuroscience to provide concrete proposals for implementing diverse teaching practice that accommodates different learning needs. Building on universal design concepts, UDL is structured around three neurological learning systems (affective, recognition, and strategic) and advocates three corresponding principles: multiple means of engagement, representation, and action/expression. Aligning with current parameters of quality education for all, UDL incorporates diversity as a fundamental premise in instructional planning to ensure equitable learning opportunities for all students. This framework enables teachers to create flexible curriculum designs that enrich learning, reduce barriers, and provide accessible educational opportunities. This research examined how digital technologies can enable UDL implementation by analyzing higher education students' perceptions. Using a quantitative methodology with a descriptive scope, data was collected through a specially designed Likert-scale questionnaire. The instrument demonstrated high reliability (Cronbachʹs α = 0.97). The sample included students from the Mexican public university system (n = 235) studying pedagogy and education. Results showed favorable perceptions of technology use in UDL across all three principles: representation (what to learn), action and expression (how to learn), and engagement (why to learn). They suggest that digital technologies can expand learning capacity and enhance skill development among university students in the UDL context. However, it should be noted that they need to be carefully integrated into educational frameworks designed and tested for their effectiveness; without such integration, their application may be ineffective or even counterproductive to learning processes. The findings demonstrate the potential of this design as a practical and theoretical model to, in line with current trends, contribute to the achievement of SDG4, promoting quality in education and learning opportunities for all. This will be helpful for institutions seeking to implement technology-enhanced UDL strategies while having broader implications for the body of research for improving higher education.